Societal Interest in The Policy Making Process: Study of Singapore’s Political Institutions Under Prime Minister Lee Hsien Loong - Ica Cahayani; Sheila Shafira Mahsyar; Oddie Bagus Saputra (Jurnal Hubungan Internasional, 2023)
This study will discuss the mainstreaming of public interest in economic policy making under the government of Prime Minister Lee Hsien Loong and the ruling People’s Action Party (PAP). Policy making, especially in making political-economic policies, is very unified and interesting, namely the public choice method, where the government or policy-making actors collect ideas that are used as national and international political economy policies based on the interests of the community through interaction with the political institutions of the People’s Action Party as a party that has been in power in Singapore since 1959. Multiracial political policies provide a change in perspective on the differences between the minority and the majority in making economic policies that tend to have no differences or barriers. The method used in this detailed study uses a systematic literature review. This research uses descriptive qualitative research method. The results show that the mainstreaming of public interest in Singapore’s economic policy making has a positive impact on the Singaporean economy. Significant economic growth is supported by the development of good public education. Keywords: Society Interest; Political Institution; Economic Policy; People’s Action Party